Molecular determinants of epithelial mesenchymal transition in mouse placenta and trophoblast stem cell - Shipra Kanti Jena; Shreya Das; Shreeta Chakraborty; Rupasri Ain (Scientific Reports, 2023)
Abstract Trophectoderm cells of the blastocyst are the precursor of the placenta that is comprised of trophoblast, endothelial and smooth muscle cells. Since trophoectoderm cells are epithelial in nature, epithelial mesenchymal transition (EMT) of trophoblast stem (TS) cells might play pivotal role in placental morphogenesis. However, the molecular regulation of EMT during placental development and trophoblast differentiation still remained elusive. In this report, we sought to identify the molecular signature that regulates EMT during placental development and TS cell differentiation in mice. On E7.5 onwards the TS cells, located in the ectoplacental cone (EPC), rapidly divide and differentiate leading to formation of placenta proper. Using a real time PCR based array of functional EMT transcriptome with RNA from mouse implantation sites (IS) on E7.5 and E9.5, it was observed that there was an overall reduction of EMT gene expression in the IS as gestation progressed from E7.5 to E9.5 albeit the levels of EMT gene expression were substantial on both days. Further validation of array results using real time PCR and western blot analysis showed significant decrease in EMT-associated genes that included (a) transcription factors (Snai2, Zeb1, Stat3 and Foxc2), (b) extracellular matrix and cell adhesion related genes (Bmp1, Itga5, Vcan and Col3A1), (c) migration and motility- associated genes (Vim, Msn and FN1) and (d) differentiation and development related genes (Wnt5b, Jag1 and Cleaved Notch-1) on E9.5. To understand whether EMT is an ongoing process during placentation, the EMT-associated signatures genes, prevalent on E 7.5 and 9.5, were analysed on E12.5, E14.5 and E17.5 of mouse placenta. Interestingly, expression of these EMT-signature proteins were significantly higher at E12.5 though substantial expressions was observed in placenta with progression of gestation from mid- to late. To evaluate whether TS cells have the potential to undergo EMT ex vivo, TS cells were subjected to EMT induction, which was confirmed using morphological analysis and marker gene expression. Induction of EMT in TS cells showed similar gene expression profile of placental EMT. These results have broad biological implications, as inadequate mesenchymal transition leading to improper trophoblast-vasculogenic mimicry leads to placental pathophysiology and pregnancy failure.